Education in Occupational Therapy: The Transition to the Academic Level. Changing the Professional Identity of Occupational Therapists in Switzerland (Journal of Medical Science, 2019)
The aim of the article is to summarise the development of the teaching and training programme for occupational therapy in the German part of Switzerland over the years 2006-2019. As the responsible program director and project manager in the transition from higher education to an academic level, the author of this article was strongly involved in changing the professional identity of occupational therapists in Switzerland. The following text presents her personal overview of this transition. The main focus lies on education, the change process and how academisation has gradually changed the curriculum in Switzerland.